TINGKAT KECEMASAN SISWA SMU DALAM MENGHADAPI UMPTN - Fadhilah, Siti Sutarmi (PAEDAGOGIA, 2008)
The purpose of this research was to know the difference of Senior High School student's anxiety level in facing the university enrollment selection (UMPTN), viewed from academic achievement, study program background, and their sexes. The descriptive method was used in this research in the causal comparative approach. The population of this research was students of Senior High School I in Mojogedang Karanganyar, and the samples were 90 students. The members of the samples were designed in purposive random sampling. The data were collected by using questionnaires and examination documents. To analyze the data, the Chi-square technique was used. The result of analysis showed that there was a different anxiety level of student viewed from academic achievement (Xh>Xt or 4,481>3,481); but if it was viewed from study program background there was no difference (Xh<Xt or 0,216<3,841); and if it was viewed from the sexes there was a difference (Xh<Xt or 2,58<3,841).